A piezoelectric ceramic and its preparation method and application
Through the two-step sintering process and the stability of the stoichiometric ratio, the density and stability of KNN-based lead-free piezoelectric ceramics are solved, and efficient and economical ceramic preparation is achieved, which is suitable for diversified and precise applications.
Patent Information
- Application Number
- CN202210117813.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-02-08
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-02-08
AI Technical Summary
The existing KNN-based lead-free piezoelectric ceramics have problems with low piezoelectric properties, density and material stability, and the traditional shape is highly brittle, making it difficult to meet the needs of sample diversification and precision.
Using a two-step sintering process, the densification sintering of piezoelectric ceramics is achieved by controlling the sintering temperature and insulation time, reducing equipment costs, and reducing the generation of miscellaneous phases through the stability of the formula stoichiometric ratio, thereby improving the density of the ceramics and Process stability.
It realizes good piezoelectric properties, density and mechanical properties of piezoelectric ceramics, while reducing equipment costs. It is suitable for production of various molding methods and different specifications and shapes, and has good process advancement and application prospects.
Smart Images

Figure CN116606140B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of piezoelectric ceramics, and in particular to a piezoelectric ceramic and a preparation method and application thereof. Background Art
[0002] In recent years, piezoelectric ceramics have been widely used in the fields of machinery and electronics due to their excellent ferroelectric and piezoelectric properties. Traditional lead zirconate titanate (PZT)-based piezoelectric ceramics have excellent piezoelectric properties and can be modified by doping to adjust device performance to meet different needs. They are currently the most widely used piezoelectric ceramics.
[0003] At present, lead-free piezoelectric ceramics can be mainly divided into three structures, namely perovskite structure, tungsten bronze structure, and bismuth layered structure. Among them, perovskite structure piezoelectric ceramics have become the most widely studied type of lead-free piezoelectric ceramics due to their excellent piezoelectric properties and compatibility of preparation process with traditional lead-based ceramic process. Common perovskite structure lead-free piezoelectric ceramics mainly include BT-based, sodium bismuth titanate (Bi 0.5 Na 0.5 TiO3, BNT) based and potassium sodium niobate (K 0.5 Na 0.5 NbO3, KNN) based systems. Among them, the Curie temperature of BT piezoelectric ceramics is relatively low (T C ≈120℃) and high sintering temperature (about 1350℃). At present, it is more used in dielectric materials due to its high dielectric properties. BNT ceramics are limited in further application due to their large coercive field (Ec≈73kV / cm) and low depolarization temperature (about 100℃) at room temperature. KNN-based lead-free piezoelectric ceramics are widely used due to their high piezoelectric properties and Curie temperature (T C ≈410℃), and is considered to be the most likely lead-free piezoelectric ceramic system to replace PZT-based piezoelectric ceramics.
[0004] However, the existing KNN-based lead-free piezoelectric ceramics have the following disadvantages: 1. The piezoelectric performance, density and material stability are relatively low; 2. Traditional KNN ceramics are mostly applied and formed in the form of sheets or blocks. These shapes are brittle, cannot withstand large impacts, cannot be applied to curved planes, are large in size, and are not easy to integrate with the matrix structure or use over a large area. With the rapid development trend of piezoelectric ceramic device applications, it is becoming increasingly difficult to meet the needs of sample diversification and precision. Summary of the invention
[0005] The object of the present invention is to provide a piezoelectric ceramic having good piezoelectric properties, mechanical properties, density and material stability.
[0006] Another object of the present invention is to provide a method for preparing a piezoelectric ceramic, which has a simple preparation process and low energy consumption. The two-step sintering process used is different from the traditional sintering process. The densification sintering of the piezoelectric ceramic can be achieved by controlling the changes in the sintering temperature and the holding time. At the same time, no complex sintering equipment such as hot pressing sintering and plasma sintering is required. Sintering densification can be achieved using an ordinary sintering furnace, which reduces the equipment cost and is conducive to industrial production. In addition, the piezoelectric ceramic preparation method of the present invention reduces the volatilization of alkali metal elements such as K and Na at high temperatures, which is conducive to the stability of the stoichiometric ratio of the formula and reduces the generation of impurities, thereby improving the density and process stability of the ceramic. It can be processed into piezoelectric ceramics of different specifications and shapes in a variety of molding methods, so it has good process advancement.
[0007] Another object of the present invention is to provide an application of a piezoelectric ceramic, which is applied to the field of laser display technology and is configured as an actuator in a laser display device.
[0008] The present invention solves the technical problem by adopting the following technical solutions.
[0009] The present invention provides a method for preparing a piezoelectric ceramic, which comprises the following steps:
[0010] Ingredients: Select raw materials and follow the chemical formula (0.96) [K 0.48 Na 0.52 Nb 0.95 Sb 0.05 O3]-0.04[(Bi 0.5 K 0.5 ) 0.9 (Li 0.5 Ce 0.5 ) 0.1 Zr (1-x) Hf (x) O3] calculate and mix ingredients to obtain the first raw material; wherein x = 0.25 to 0.75;
[0011] Ball milling: ball milling the first raw material to obtain a first sample;
[0012] Pre-sintering: keeping the first sample at 850-950° C. for 6-10 hours to obtain a second sample;
[0013] Molding: molding the second sample according to a target molding form to obtain a molded third sample;
[0014] Debinding: the third sample is kept at 500-950° C. for debinding to obtain a fourth sample;
[0015] Sintering: sintering the fourth sample to obtain a fifth sample;
[0016] Silver electrode: brush silver paste on the surface of the fifth sample, and then keep it at 500-900° C. for 10-40 minutes to obtain a sixth sample;
[0017] High-voltage polarization: the sixth sample is placed in a constant temperature environment of 20-90° C., and a high voltage of 2-4 kV is applied for polarization, and the pressure holding time is 15-30 min.
[0018] Optionally, in a preferred embodiment of the present invention, the third sample is a piezoelectric ceramic sheet;
[0019] The forming process of the piezoelectric ceramic sheet includes: grinding the second sample, and then granulating and pressing the sample in sequence to obtain the third sample;
[0020] The sintering process of the piezoelectric ceramic sheet includes: keeping the fourth sample at 1100-1200°C for 1-15 minutes, cooling it to 900-1060°C, and then keeping it for 3-25 hours to obtain a fifth sample; wherein, during the process of cooling to 900-1060°C, the cooling rate is 5-20°C / min.
[0021] Furthermore, in a preferred embodiment of the present invention, a binder polyvinyl alcohol solution with a mass fraction of 5-12% is added when the second sample is ground and granulated.
[0022] Optionally, in a preferred embodiment of the present invention, the third sample is a piezoelectric ceramic tube;
[0023] The molding process of the piezoelectric ceramic tube includes: adding an adhesive and a plasticizer to the powdered second sample to mix the materials, and then performing extrusion molding; wherein the mass ratio of the second sample, the adhesive and the plasticizer is 98-102:3-7:18-22;
[0024] The sintering process of the piezoelectric ceramic tube includes: keeping the fourth sample at 1140-1200°C for 1-20 minutes, cooling it to 900-1040°C, and then keeping it for 3-25 hours to obtain a fifth sample; wherein, during the process of cooling to 900-1040°C, the cooling rate is 5-20°C / min.
[0025] Furthermore, in a preferred embodiment of the present invention, the adhesive is a polyvinyl alcohol aqueous solution, and the plasticizer is cellulose.
[0026] Furthermore, in a preferred embodiment of the present invention, the mass ratio of the second sample, the adhesive and the plasticizer is 100:5:20.
[0027] Optionally, in a preferred embodiment of the present invention, x=0.45-0.65.
[0028] Optionally, in a preferred embodiment of the present invention, when the first sample is subjected to ball milling treatment, anhydrous ethanol is first added to the first sample and then the ball milling treatment is performed, the ball milling time is 8-24 hours, and the corresponding ball mill speed is 150-500 rpm;
[0029] The method for preparing the piezoelectric ceramic further includes: aging the piezoelectric ceramic obtained after the high-voltage polarization at room temperature for 24 hours, and then performing a performance test.
[0030] The present invention also provides a piezoelectric ceramic, which is prepared according to the preparation method of the piezoelectric ceramic.
[0031] The present invention further proposes an application of the piezoelectric ceramic as described above, wherein the piezoelectric ceramic is applied to the field of display technology, and the field of display technology is the field of laser display technology;
[0032] The laser display technology includes a laser display device, the laser display device includes a fiber scanner, the fiber scanner includes an actuator, and the piezoelectric ceramic is configured as the actuator.
[0033] The piezoelectric ceramics and their preparation methods and applications provided by the embodiments of the present invention have the following beneficial effects: the preparation method of the piezoelectric ceramics provided by the embodiments of the present invention adopts a two-step sintering process that is different from the traditional sintering process, and can achieve densification sintering of the piezoelectric ceramics by controlling the changes in the sintering temperature and the holding time, and does not require complex sintering equipment such as hot pressing sintering and plasma sintering, and can achieve sintering densification with an ordinary sintering furnace, thereby reducing equipment costs and being conducive to industrial production; in addition, the preparation method of the piezoelectric ceramics provided by the embodiments of the present invention reduces the volatilization of alkali metal elements such as K and Na at high temperatures, which is conducive to the stability of the stoichiometric ratio of the formula, reduces the generation of impurities, and thus improves the density and process stability of the ceramics; the piezoelectric ceramics provided by the present invention have high piezoelectric properties, density and mechanical properties, and are also environmentally friendly. The piezoelectric ceramic preparation method of the present invention can be processed into piezoelectric ceramics of different specifications and shapes in a variety of molding methods, so it has good process advancement; when the piezoelectric ceramics provided by the present invention are applied to the field of laser display technology, they can be configured as actuators in laser scanning devices, have good piezoelectric driving performance and stability, and have good and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0035] Figure 1 A physical picture of the KNNS-BKLCZ(1-x)Hx piezoelectric ceramic sheet and the piezoelectric ceramic hollow circular tube provided in the embodiments of the present invention;
[0036] Figure 2 XRD diagram of the KNNS-BKLCZ(1-x)Hx piezoelectric ceramic sheet provided in an embodiment of the present invention;
[0037] Figure 3 SEM image of the KNNS-BKLCZ(1-x)Hx piezoelectric ceramic sheet provided in an embodiment of the present invention;
[0038] Figure 4 The piezoelectric properties and Curie temperature diagram of the KNNS-BKLCZ(1-x)Hx piezoelectric ceramic sheet provided in the embodiment of the present invention;
[0039] FIG5 is a dielectric temperature curve of a KNNS-BKLCZ(1-x)Hx piezoelectric ceramic sheet provided in an embodiment of the present invention, wherein: Figure 5a , Figure 5b , Figure 5c , Figure 5d , Figure 5e and Figure 5f , respectively represent the dielectric-temperature curves of KNNS-BKLCZ(1-x)Hx piezoelectric ceramics when x is 0.25, 0.35, 0.45, 0.55, 0.65 and 0.75;
[0040] Figure 6 The dielectric loss and dielectric constant of the KNNS-BKLCZ(1-x)Hx piezoelectric ceramic sheet are obtained according to the dielectric-temperature curve of FIG5 ;
[0041] Figure 7 The mechanical quality factor Qm and electromechanical coupling coefficient kp of the KNNS-BKLCZ(1-x)Hx piezoelectric ceramic sheet provided in the embodiment of the present invention;
[0042] Figure 8 This is a SEM image of a ceramic tube prepared by extrusion molding of KNNS-BKLCZ(1-x)Hx piezoelectric ceramic powder when x=0.55 provided in an embodiment of the present invention;
[0043] Fig. 9This is the XRD pattern of the KNNS-BKLCZ(1-x)Hx piezoelectric ceramic provided in the embodiment of the present invention when x=0.55 and is prepared into a ceramic tube by extrusion molding. DETAILED DESCRIPTION
[0044] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0045] The piezoelectric ceramics according to the embodiments of the present invention and their preparation methods and applications are described in detail below.
[0046] An embodiment of the present invention provides a method for preparing a piezoelectric ceramic, comprising the following steps:
[0047] S1. Ingredients: Select raw materials according to the chemical formula (0.96) [K 0.48 Na 0.52 Nb 0.95 Sb 0.05 O3]-0.04[(Bi 0.5 K 0.5 ) 0.9 (Li 0.5 Ce 0.5 ) 0.1 Zr (1-x) Hf (x) O3] to calculate and mix the ingredients to obtain the first raw material; wherein x represents Hf + The molar amount of x = 0.25 ~ 0.75; [(Bi 0.5 K 0.5 ) 0.9 (Li 0.5 Ce 0.5 ) 0.1 Zr (1-x) Hf (x) O3] in the component, in other embodiments, it is not necessarily K element, but may be other alkali metal elements, such as sodium and thiophene. It should be noted that in the embodiment of the present invention, according to the chemical formula (0.96) [K 0.48 Na 0.52 Nb 0.95 Sb 0.05 O3]-0.04[(Bi 0.5 K 0.5 ) 0.9 (Li 0.5 Ce 0.5 ) 0.1 Zr (1-x) Hf (x)O3] When calculating and mixing, the purity of the selected raw materials corresponding to each element must be greater than 99%, and optionally, the raw material for providing the Na element may be Na2CO3, the raw material for providing the K element may be K2CO3, the raw material for providing the Nb element may be Nb2O5, the raw material for providing the Sb element may be Sb2O3, the raw material for providing the Bi element may be Bi2O3, the raw material for providing the Li element may be Li2CO3, the raw material for providing the Ce element may be CeO2, the raw material for providing the Zr element may be ZrO2, and the raw material for providing the Hf element may be HfO2. It should be emphasized that in other embodiments of the present invention, it is not limited to the raw materials corresponding to each element provided in the embodiments of the present invention, and it can also be other raw materials corresponding to each element, as long as it can provide the corresponding element for the first raw material.
[0048] Optionally, in a preferred embodiment of the present invention, x=0.25, 0.35, 0.45, 0.55, 0.65 or 0.75. It should be noted that, in addition to x=0.25, 0.35, 0.45, 0.55, 0.65 or 0.75 in the embodiment of the present invention, in other embodiments of the present invention, x can also be any value between 0.25 and 0.75, such as 0.3, 0.4, 0.5, 0.6 and 0.7. It should be emphasized that, in an embodiment of the present invention, x=0.45 to 0.65.
[0049] Further, for the convenience of describing the embodiments of the present invention, the chemical formula constructed by the raw material formula provided in the embodiments of the present invention is (0.96)[K 0.48 Na 0.52 Nb 0.95 Sb 0.05 O3]-0.04[(Bi 0.5 K 0.5 ) 0.9 (Li 0.5 Ce 0.5 ) 0.1 Zr (1-x) Hf (x) O3], which can be abbreviated as KNNS-BKLCZ(1-x)Hx. It should be emphasized that by selecting the raw materials according to the molar number during the batching process, the specific formula of the first raw material is controlled from the elements and the corresponding ratio. + and Ce 4+ Add to (Bi 0.5 K 0.5 )Zr(1-x)Hf(x)O3 to obtain the second component [(Bi 0.5 K 0.5 ) 0.9 (Li 0.5 Ce 0.5 )0.1 Zr(1-x)Hf(x)O3], and Sb 5+ Elements are added to achieve the modification of KNNS-based piezoelectric ceramics, which provides a good material structure foundation for the excellent properties of the final piezoelectric ceramics.
[0050] S2, ball milling: ball milling the first raw material to obtain a first sample. It should be noted that by ball milling the first raw material, the powder dispersibility of the first raw material can be better and the specific surface area can be larger, so as to facilitate the pre-sintering in the next step. It should be emphasized that in the preferred embodiment of the present invention, when ball milling the first sample, anhydrous ethanol is first added to the first sample to fully dissolve and disperse the first raw material, and then ball milling is performed. The ball milling time is limited to 8-24h, and the corresponding ball mill speed is limited to 150-500 rpm to ensure the best ball milling effect.
[0051] S3, pre-sintering: the first sample is kept at 850-950°C for 6-10 hours to obtain a second sample. It should be noted that pre-sintering is a heat treatment process for the first sample, which is intended to improve the composition and microstructure of the first sample, which can increase subsequent processing efficiency and reduce processing costs.
[0052] S4, molding: molding the second sample according to the target molding shape to obtain a molded third sample.
[0053] Optionally, in a preferred embodiment of the present invention, the third sample is a piezoelectric ceramic sheet, that is, the target forming form is a sheet. Specifically, the forming process of the piezoelectric ceramic sheet includes: grinding the second sample, granulating and tableting in sequence to obtain the third sample. It should be noted that when the second sample is ground and granulated, a binder polyvinyl alcohol solution with a mass fraction of 5-12% is also added. Adding a binder can help granulation and tableting. And in other embodiments of the present invention, the binder is not limited to polyvinyl alcohol solution, but can also be other binders.
[0054] Optionally, in a preferred embodiment of the present invention, the third sample can also be a piezoelectric ceramic tube. Specifically, the molding process of the piezoelectric ceramic tube includes: adding an adhesive and a plasticizer to the powdered second sample for mixing, and then extruding and molding; wherein the mass ratio of the second sample, the adhesive and the plasticizer is 98-102:3-7:18-22. Optionally, the adhesive is a polyvinyl alcohol aqueous solution, and the plasticizer is cellulose. Preferably, the mass ratio of the second sample, the adhesive and the plasticizer is 100:5:20. It should be noted that the reason why the mass ratio of the second sample, the adhesive and the plasticizer is preferably limited in the embodiment of the present invention is that their relative ratio determines the piezoelectric properties and comprehensive mechanical properties of the piezoelectric ceramic tube, and it is crucial to whether it can be extruded smoothly and stably.
[0055] S5, debinding: the third sample is kept at 500-950°C for debinding to obtain a fourth sample. It should be noted that the purpose of debinding is to remove the binder, adhesive and plasticizer added during molding after molding.
[0056] S6. Sintering: sinter the fourth sample to obtain a fifth sample.
[0057] Specifically, when formed into a piezoelectric ceramic sheet, the sintering process of the piezoelectric ceramic sheet includes: keeping the fourth sample at 1100-1200°C for 1-15 minutes, cooling to 900-1060°C, and then keeping it for 3-25 hours to obtain the fifth sample; wherein, in the process of cooling to 900-1060°C, the cooling rate is 5-20°C / min.
[0058] Furthermore, when formed into a piezoelectric ceramic tube, the sintering process of the piezoelectric ceramic tube includes: keeping the fourth sample at 1140-1200°C for 1-20 minutes, cooling it to 900-1040°C, and then keeping it for 3-25 hours to obtain the fifth sample; wherein, in the process of cooling to 900-1040°C, the cooling rate is 5-20°C / min.
[0059] It should be noted that the S6 sintering process is an important step in sintering the fourth sample into porcelain. Its heat preservation parameters and cooling parameters are important indicators in the sintering process, which determine the essential properties of the fifth sample as a ceramic. In order to optimize and control the good performance of the fifth sample as a piezoelectric ceramic, during sintering, the embodiment of the present invention requires that the cooling rate be limited to 5-20°C / min during the cooling process to 900-1040°C (this cooling rate can inhibit the grain boundary migration after the formation of a connected skeleton between particles in the ceramic microstructure, and use the grain boundary diffusion effect to make the ceramic sample fully dense).
[0060] It is further necessary to emphasize that the above two-step sintering method provided by the embodiment of the present invention has a good advantage over the traditional solid phase method. Specifically, for the traditional solid phase method sintering, since high temperature and long-term heat preservation are required, the pores and grain boundaries can move together, resulting in the gradual growth of the grains and the gradual shrinkage of the pores, thereby improving the density. However, in the later stage of sintering, due to the bridging effect between the grain boundaries, the migration rate of the pores is reduced, and even the phenomenon of being pinned occurs. At this time, the pores leave the grain boundaries and are surrounded by the grains, resulting in the lengthening of the diffusion path of the material and the reduction of the diffusion rate, making it almost impossible to further shrink and eliminate the pores. Further sintering in this case is difficult to improve the density of the ceramic. On the contrary, the grain size will continue to grow, and even a few grains will grow abnormally, so that the residual small pores are more wrapped in the depth of the large grains, which is not good for the performance and use of the ceramic. The two-step sintering of the new process provided by the embodiment of the present invention does not require high temperature and long-term heat preservation, and the abnormal growth of grains can be eliminated. Specifically, the first step of the two-step sintering can achieve a subcritical unstable state of pores in the ceramic, providing an important basic condition for the subsequent second step of low-temperature sintering. However, for the second step of low-temperature sintering, the ceramic particles are "frozen", and the grain boundaries form a "bridge" structure, which restricts the migration of pores and grain boundaries. Under long-term heat preservation, since the activation energy of grain boundary diffusion is less than the activation energy of grain boundary migration, grain boundary diffusion becomes the main mechanism of ceramic densification, which plays an important role in obtaining grains of uniform size.
[0061] S7, silvering the electrode: brush the surface of the fifth sample with silver paste, and then keep it at 500-900°C for 10-40 minutes to obtain the sixth sample. It should be noted that in other embodiments of the present invention, the electrode can also be silvered by silver layer infiltration, chemical deposition and vacuum coating.
[0062] S8, high voltage polarization: the sixth sample is placed in a constant temperature environment of 20-90°C, and a high voltage of 2-4kV is applied for polarization, and the pressure holding time is 15-30min. It should be noted that through high voltage polarization, the electric domains inside the ceramic are oriented, so that the piezoelectric properties of the ceramic are maximized.
[0063] Furthermore, the preparation method of the piezoelectric ceramic provided in the embodiment of the present invention also includes an aging test, that is: the piezoelectric ceramic obtained after high-voltage polarization is aged at room temperature for 24 hours, and then a performance test is performed (after aging is stable, various indicators are tested to see whether the expected performance requirements are met).
[0064] It should be emphasized that in the piezoelectric ceramic preparation method provided in the embodiment of the present invention, all parameter values involving the parameter range can be any point value in the corresponding parameter range, and are not limited to the point value or preferred value given as an example in this embodiment. For example, during the ball milling process, the ball milling time is limited to 8-24h, and the corresponding ball mill speed is limited to 150-500 rpm. The corresponding representation is that the ball milling time can be any duration in the range of 8-24h (such as 8.5 hours, 9 hours or 10 hours, etc.), and the ball mill speed is any speed in the parameter range of 150-500 rpm (such as 160 rpm, 182 rpm, 265 rpm, etc.). The point values in the parameter range cannot be listed one by one in the embodiments in the specification of this application, so the corresponding parameter range actually represents every point value in the parameter range. Therefore, all parameter adjustment examples are no longer given in the embodiment part of this specification.
[0065] The present invention also provides a piezoelectric ceramic, which is prepared according to the preparation method of the piezoelectric ceramic provided by the above embodiment of the present invention. The piezoelectric ceramic provided by the embodiment of the present invention has high piezoelectric performance, density and mechanical properties, and is also environmentally friendly.
[0066] The present invention also proposes an application of a piezoelectric ceramic as provided in the above embodiment of the present invention, the piezoelectric ceramic is applied to the field of display technology, optionally, the field of display technology is the field of laser display technology. It should be noted that the laser display technology includes a laser display device, the laser display device includes a fiber scanner, the fiber scanner includes an actuator, the piezoelectric ceramic is configured as the actuator, and the actuator uses the inverse piezoelectric effect of the piezoelectric ceramic to control the optical fiber on the actuator to vibrate and scan, thereby realizing laser scanning imaging.
[0067] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0068] Example 1
[0069] This embodiment provides a method for preparing a piezoelectric ceramic, and the specific preparation process is as follows:
[0070] 1. Ingredients: According to the selected raw materials and molar mass, according to the formula chemical formula (0.96) [K 0.48 Na 0.52 Nb 0.95 Sb 0.05 O3]-0.04[(Bi 0.5 K 0.5 ) 0.9 (Li 0.5 Ce 0.5 ) 0.1 Zr (1-x) Hf(x) O3] to calculate and mix the ingredients to obtain the first raw material; wherein x represents Hf + Molar amount, x = 0.25.
[0071] 2. Ball milling: ball mill the first raw material to obtain a first sample. Specifically, the prepared first raw material is placed in a ball milling jar containing ball milling beads, anhydrous ethanol is added, and the mixture is transferred to a ball mill for ball milling for 8-24 hours at a rotation speed of 150-500 rpm.
[0072] 3. Pre-burning: transfer the first sample to a muffle furnace and set the program to keep warm at 850-950°C for 6-10 hours to obtain a second sample.
[0073] 4. Granulation and tableting: The second sample is placed in a mortar, finely ground, a binder PVA solution (5-12 wt%) is added for granulation, and the mixture is poured into a mold having a diameter of 10-15 mm, and tableted at a pressure of 10-20 MPa using a powder tablet press to obtain a third sample.
[0074] 5. Debinding: The third sample is transferred to a debinding furnace and kept at 500-950°C for debinding to obtain a fourth sample;
[0075] 6. Sintering: The fourth sample is sintered by a two-step sintering method to obtain a fifth sample; specifically, the first step sintering temperature is 1100-1200°C, kept warm for 1-15 minutes, and then quickly cooled to 900-1060°C, kept warm for 3-25 hours.
[0076] 7. Silver electrode: brush the upper and lower surfaces of the fifth sample obtained after sintering with silver paste, and then keep it at 500-900℃ for 10-40min to obtain the sixth sample;
[0077] 8. High-voltage polarization: Place the sixth sample in a constant-temperature silicone oil bath at 20-90°C, apply a high voltage of 2-4kV for polarization, and maintain the voltage for 15-30min. It should be noted that electrical performance testing can only be performed after aging at room temperature for 24h after polarization.
[0078] This embodiment also provides a piezoelectric ceramic, which is prepared by the preparation method of the piezoelectric ceramic provided by this embodiment.
[0079] This embodiment also provides an application of the piezoelectric ceramic as described above, which is applied to the field of laser display technology. Specifically, the laser display technology includes a laser display device, the laser display device includes a fiber scanner, the fiber scanner includes an actuator, and the actuator is prepared by the piezoelectric ceramic provided in this embodiment. It should be noted that the actuator controls the optical fiber on the actuator to perform vibration scanning through the inverse piezoelectric effect principle of the piezoelectric ceramic.
[0080] Example 2
[0081] The piezoelectric ceramic and the preparation method thereof provided in this embodiment are substantially the same as those provided in embodiment 1, except that the ratio of the formula used in the preparation process of the piezoelectric ceramic provided in this embodiment is different from that in embodiment 1. + The molar amount x is 0.35.
[0082] Example 3
[0083] The piezoelectric ceramic and the preparation method thereof provided in this embodiment are substantially the same as those provided in embodiment 1, except that the ratio of the formula used in the preparation process of the piezoelectric ceramic provided in this embodiment is different from that in embodiment 1. + The molar amount x is 0.45.
[0084] Example 4
[0085] The piezoelectric ceramic and the preparation method thereof provided in this embodiment are substantially the same as those provided in embodiment 1, except that the ratio of the formula used in the preparation process of the piezoelectric ceramic provided in this embodiment is different from that in embodiment 1. + The molar amount x is 0.55.
[0086] Example 5
[0087] The piezoelectric ceramic and the preparation method thereof provided in this embodiment are substantially the same as those provided in embodiment 1, except that the ratio of the formula used in the preparation process of the piezoelectric ceramic provided in this embodiment is different from that in embodiment 1. + The molar amount x is 0.65.
[0088] Example 6
[0089] The piezoelectric ceramic and the preparation method thereof provided in this embodiment are substantially the same as those provided in embodiment 1, except that the ratio of the formula used in the preparation process of the piezoelectric ceramic provided in this embodiment is different from that in embodiment 1. + The molar amount x is 0.75.
[0090] Example 7
[0091] This embodiment provides a method for preparing a piezoelectric ceramic, and the specific preparation process is as follows:
[0092] 1. Ingredients: According to the selected raw materials and molar mass, according to the formula chemical formula (0.96) [K 0.48 Na 0.52 Nb 0.95 Sb0.05 O3]-0.04[(Bi 0.5 K 0.5 ) 0.9 (Li 0.5 Ce 0.5 ) 0.1 Zr (1-x) Hf (x) O3] to calculate and mix the ingredients to obtain the first raw material; wherein x represents Hf + Molar amount, x = 0.25.
[0093] 2. Ball milling: ball mill the first raw material to obtain a first sample. Specifically, the prepared first raw material is placed in a ball milling jar containing ball milling beads, anhydrous ethanol is added, and the mixture is transferred to a ball mill for ball milling for 8-24 hours at a rotation speed of 150-500 rpm.
[0094] 3. Pre-burning: transfer the first sample to a muffle furnace and set the program to keep warm at 850-950°C for 6-10 hours to obtain a second sample.
[0095] 4. Mixing: Put the second sample into a mortar, grind it finely, and add PVA aqueous solution (5-12wt%) as a binder and cellulose as a plasticizer, and mix the second sample ground powder, plasticizer, and binder in a mass ratio of 100:5:20.
[0096] 5. Extrusion molding: The mixed material is put into an extruder for extrusion molding, and extruded into a hollow circular tube with inner and outer diameters of 1.5-2.0 mm and 2.4-3 mm, respectively, and a length of 10-100 mm, to obtain a third sample.
[0097] 6. Debinding: The third sample is transferred to a debinding furnace and kept at 500-950°C for debinding to obtain a fourth sample.
[0098] 7. Sintering: The fourth sample is sintered by a two-step sintering method to obtain a fifth sample; specifically, the first step sintering temperature is 1140-1200°C, kept warm for 1-20 minutes, and then quickly cooled to 900-1040°C, kept warm for 3-25 hours.
[0099] 8. Silver electrode: brush silver paste on the surface of the fifth sample obtained after sintering, and then keep it at 500-900℃ for 10-40min to obtain the sixth sample;
[0100] 9. High-voltage polarization: Place the sixth sample in a constant-temperature silicone oil bath at 20-90°C, apply a high voltage of 2-4kV for polarization, and maintain the voltage for 15-30min. It should be noted that electrical performance testing can only be performed after aging at room temperature for 24h after polarization.
[0101] This embodiment also provides a piezoelectric ceramic, which is prepared by the preparation method of the piezoelectric ceramic provided by this embodiment.
[0102] This embodiment also provides an application of the piezoelectric ceramic as described above, which is applied to the field of laser display technology. Specifically, the laser display technology includes a laser display device, the laser display device includes a fiber scanner, the fiber scanner includes an actuator, and the actuator is prepared by the piezoelectric ceramic provided in this embodiment. It should be noted that the actuator controls the optical fiber on the actuator to perform vibration scanning through the inverse piezoelectric effect principle of the piezoelectric ceramic.
[0103] Example 8
[0104] The piezoelectric ceramics and preparation methods provided in this embodiment are substantially the same as those provided in embodiment 7, except that the ratio of the formula used in the preparation process of the piezoelectric ceramics provided in this embodiment is different from that in embodiment 7. + The molar amount x is 0.35.
[0105] Example 9
[0106] The piezoelectric ceramics and preparation methods provided in this embodiment are substantially the same as those provided in embodiment 7, except that the ratio of the formula used in the preparation process of the piezoelectric ceramics provided in this embodiment is different from that in embodiment 7. + The molar amount x is 0.45.
[0107] Example 10
[0108] The piezoelectric ceramics and preparation methods provided in this embodiment are substantially the same as those provided in embodiment 7, except that the ratio of the formula used in the preparation process of the piezoelectric ceramics provided in this embodiment is different from that in embodiment 7. + The molar amount x is 0.55.
[0109] Embodiment 11
[0110] The piezoelectric ceramics and preparation methods provided in this embodiment are substantially the same as those provided in embodiment 7, except that the ratio of the formula used in the preparation process of the piezoelectric ceramics provided in this embodiment is different from that in embodiment 7. + The molar amount x is 0.65.
[0111] Example 12
[0112] The piezoelectric ceramics and preparation methods provided in this embodiment are substantially the same as those provided in embodiment 7, except that the ratio of the formula used in the preparation process of the piezoelectric ceramics provided in this embodiment is different from that in embodiment 7.+ The molar amount x is 0.75.
[0113] Further, in order to verify and illustrate the technical effects of the piezoelectric ceramics provided by the embodiments of the present invention and their preparation and application, this application is described through some example samples provided by the present invention, specifically:
[0114] First, please refer to Figure 2 , Figure 2 The XRD patterns corresponding to the KNNS-BKLCZ(1-x)Hx piezoelectric ceramics provided in the embodiment of the present invention when x is different values are shown in FIG. Figure 2 It can be seen from the analysis that KNNS-BKLCZ(1-x)Hx piezoelectric ceramics have a single perovskite structure at room temperature, which indicates that the doping of BKLCZ(1-x)Hx makes KNNS-BKLCZ(1-x)Hx piezoelectric ceramics form a stable solid solution structure. In addition, when x is in the range of 0.45-0.65, KNNS-BKLCZ(1-x)Hx piezoelectric ceramics have a RT multiphase coexistence crystal structure at room temperature, and the crystal structure is stable. When x<0.45 or x>0.65, the phase structure of KNNS-BKLCZ(1-x)Hx piezoelectric ceramics changes, and the double peak becomes a single peak. KNNS-BKLCZ(1-x)Hx piezoelectric ceramics are mainly R phase structures, and the piezoelectric properties will also change accordingly.
[0115] For further information, please refer to Figure 3 , Figure 3 The SEM images of the KNNS-BKLCZ(1-x)Hx piezoelectric ceramics are provided for the embodiments of the present invention. When x=0.45 and 0.55, the KNNS-BKLCZ(1-x)Hx piezoelectric ceramics have a dense crystal structure, mainly composed of large grains of 20-30 μm and small grains of 3-5 μm filling the gaps between the large grains. The results are also consistent with the analysis results of the XRD graph, that is, when x changes, the phase structure of the KNNS-BKLCZ(1-x)Hx piezoelectric ceramics changes, thereby changing the crystal structure and density of the ceramics. This indicates that the Zr in the second component BKLCZ(1-x)Hx 4+ / Hf + It directly affects the phase structure and crystal structure of KNNS-BKLCZ(1-x)Hx piezoelectric ceramics.
[0116] For further information, please refer to Figure 4 , Figure 4The piezoelectric properties and Curie temperature of KNNS-BKLCZ(1-x)Hx piezoelectric ceramics are provided for the embodiments of the present invention. When x=0.55, KNNS-BKLCZH ceramics have the best piezoelectric properties, i.e., d33=520±20pC / N, and have a relatively high Curie temperature of 216°C. Combined with the above XRD / SEM analysis results, it can be seen that when x=0.55, KNNS-BKLCZ(1-x)Hx piezoelectric ceramics have a stable RT multiphase coexistence crystal structure with good crystal structure density, thereby having relatively high piezoelectric properties and Curie temperature.
[0117] Further, please continue to refer to Figure 5 and Figure 6 5 is a dielectric-temperature curve of a KNNS-BKLCZ(1-x)Hx piezoelectric ceramic provided by an embodiment of the present invention, from which the Curie temperature and dielectric loss of the ceramic can be obtained; Figure 6 The dielectric loss and dielectric constant of KNNS-BKLCZ(1-x)Hx piezoelectric ceramics are obtained according to the dielectric temperature curve of Figure 5. When x = 0.55, KNNS-BKLCZ(1-x)Hx piezoelectric ceramics have the lowest dielectric loss (tanδ = 0.2712) and a higher dielectric constant (ε γ =2905).
[0118] For further information, please refer to Figure 7 , Figure 7 The mechanical quality factor Qm and electromechanical coupling coefficient kp of the KNNS-BKLCZ(1-x)Hx piezoelectric ceramic are provided for the embodiment of the present invention. From the data, it can be seen that when x=0.55, the KNNS-BKLCZ(1-x)Hx piezoelectric ceramic has the best mechanical properties, that is, Q m =29, k p =0.64, which shows that KNNS-BKLCZ(1-x)Hx piezoelectric ceramics have a higher electromechanical coupling coefficient, which is comparable to the dielectric properties of PZT piezoelectric ceramics. Combined with the data of higher piezoelectric properties and Curie temperature, it can be judged that this lead-free piezoelectric ceramic system has broad application prospects.
[0119] Finally, please refer to Figure 8 and Fig. 9 , Figure 8 When x=0.55, the SEM image of the ceramic tube prepared by extrusion molding of KNNS-BKLCZ(1-x)Hx piezoelectric ceramic powder is shown in FIG. Figure 8 It can be seen that the ceramic system can be made into a denser KNN lead-free piezoelectric ceramic tube; Fig. 9 The embodiment of the present invention provides an XRD pattern of the KNNS-BKLCZ(1-x)Hx piezoelectric ceramic as a piezoelectric ceramic tube. Fig. 9It can be seen that the lead-free piezoelectric ceramic tube shows a single perovskite structure without the presence of a second phase, indicating that the second component BKLCZ 0.45 H 0.55 It has completely entered the lattice of KNN ceramics. At the same time, the diffraction peak at about 46° judges that the ceramic is an RT multiphase coexistence structure. It can be seen that the lead-free piezoelectric ceramic tube and the piezoelectric ceramic sheet have the same phase structure.
[0120] In summary, the KNNS-BKLCZ(1-x)Hx piezoelectric ceramics provided in the embodiments of the present invention have a stable crystal structure and high piezoelectric performance, that is, d 33 =520±20pC / N, T C =216℃,tanδ=0.02712,ε γ =2905, Qm=29, kp=0.64; at the same time, the KNNS-BKLCZ(1-x)Hx piezoelectric ceramics provided in the embodiment of the present invention can be prepared by a corresponding preparation method to obtain ceramic pre-sintered powder and then an extrusion molding process to prepare a KNNS-BKLCZ(1-x)Hx-based lead-free piezoelectric ceramic tube, which has the same density and phase structure as the ceramic sheet. Compared with the piezoelectric ceramic sheet, the hollow round ceramic tube is more conducive to integrated assembly, has better flexibility and deflection, and has great application prospects in the research field of electronic devices such as actuators and resonators.
[0121] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A method for preparing a piezoelectric ceramic sheet, characterized in that: It includes the following steps: Ingredients: Select raw materials and follow the chemical formula (0.96) [K 0.48 Na 0.52 Nb 0.95 Sb 0.05 O3]-0.04[(Bi 0.5 K 0.5 ) 0.9 (Li 0.5 Ce 0.5 ) 0.1 Zr (1-x) Hf (x) O3] calculate and mix ingredients to obtain a first raw material; wherein x = 0.45 to 0.55; Ball milling: ball milling the first raw material to obtain a first sample; Pre-sintering: keeping the first sample at 850-950° C. for 6-10 hours to obtain a second sample; Molding: molding the second sample according to a target molding form to obtain a molded third sample, wherein the third sample is a piezoelectric ceramic sheet; Debinding: the third sample is kept at 500-950° C. for debinding to obtain a fourth sample; Sintering: After the fourth sample is kept at 1100-1200° C. for 1-15 min, the temperature is reduced to 900-1060° C., and the temperature is further maintained for 3-25 h to obtain a fifth sample; wherein, during the process of reducing the temperature to 900-1060° C., the cooling rate is 5-20° C. / min; Silver electrode: brush silver paste on the surface of the fifth sample, and then keep it at 500-900° C. for 10-40 minutes to obtain a sixth sample; High-voltage polarization: the sixth sample is placed in a constant temperature environment of 20-90° C., and a high voltage of 2-4 kV is applied for polarization, and the pressure holding time is 15-30 min.
2. The method for preparing a piezoelectric ceramic sheet according to claim 1, characterized in that: The forming process of the piezoelectric ceramic sheet includes: grinding the second sample, and then granulating and pressing the sample in sequence to obtain the third sample.
3. The method for preparing a piezoelectric ceramic sheet according to claim 2, characterized in that: When the second sample is ground and granulated, a binder polyvinyl alcohol solution with a mass fraction of 5-12% is added.
4. The method for preparing a piezoelectric ceramic sheet according to claim 1, characterized in that: When the first sample is subjected to ball milling treatment, anhydrous ethanol is first added to the first sample and then the ball milling treatment is performed. The ball milling time is 8-24 hours, and the corresponding ball mill speed is 150-500 revolutions per minute. The method for preparing the piezoelectric ceramic sheet further includes: aging the piezoelectric ceramic obtained after the high-voltage polarization at room temperature for 24 hours, and then performing a performance test.
5. A piezoelectric ceramic sheet, characterized in that: The piezoelectric ceramic sheet is prepared according to the method for preparing a piezoelectric ceramic sheet according to any one of claims 1 to 4.
6. An application of the piezoelectric ceramic sheet as claimed in claim 5, characterized in that: The piezoelectric ceramic sheet is applied in the field of display technology, and the field of display technology is the field of laser display technology; The laser display technology includes a laser display device, the laser display device includes a fiber scanner, the fiber scanner includes an actuator, and the piezoelectric ceramic sheet is configured as the actuator.
7. A method for preparing a piezoelectric ceramic tube, characterized in that: It includes the following steps: Ingredients: Select raw materials and follow the chemical formula (0.96) [K 0.48 Na 0.52 Nb 0.95 Sb 0.05 O3]-0.04[(Bi 0.5 K 0.5 ) 0.9 (Li 0.5 Ce 0.5 ) 0.1 Zr (1-x) Hf (x) O3] calculate and mix ingredients to obtain a first raw material; wherein x = 0.45 to 0.55; Ball milling: ball milling the first raw material to obtain a first sample; Pre-sintering: keeping the first sample at 850-950° C. for 6-10 hours to obtain a second sample; Molding: molding the second sample according to a target molding form to obtain a molded third sample, wherein the third sample is a piezoelectric ceramic tube; Debinding: the third sample is kept at 500-950° C. for debinding to obtain a fourth sample; Sintering: After the fourth sample is kept at 1140-1200° C. for 1-20 min, the temperature is reduced to 900-1040° C., and the temperature is further maintained for 3-25 h to obtain a fifth sample; wherein, during the process of reducing the temperature to 900-1040° C., the cooling rate is 5-20° C. / min; Silver electrode: brush silver paste on the surface of the fifth sample, and then keep it at 500-900° C. for 10-40 minutes to obtain a sixth sample; High-voltage polarization: the sixth sample is placed in a constant temperature environment of 20-90° C., and a high voltage of 2-4 kV is applied for polarization, and the pressure holding time is 15-30 min.
8. The method for preparing a piezoelectric ceramic tube according to claim 7, characterized in that: The molding process of the piezoelectric ceramic tube includes: adding an adhesive and a plasticizer to the powdered second sample for mixing, and then performing extrusion molding; wherein the mass ratio of the second sample, the adhesive and the plasticizer is 98-102:3-7:18-22.
9. The method for preparing a piezoelectric ceramic tube according to claim 8, characterized in that: The adhesive is a polyvinyl alcohol aqueous solution, and the plasticizer is cellulose.
10. The method for preparing a piezoelectric ceramic tube according to claim 8, characterized in that: The mass ratio of the second sample, the adhesive and the plasticizer is 100:5:
20.
11. The method for preparing a piezoelectric ceramic tube according to claim 7, characterized in that: When the first sample is subjected to ball milling treatment, anhydrous ethanol is first added to the first sample and then the ball milling treatment is performed. The ball milling time is 8-24 hours, and the corresponding ball mill speed is 150-500 revolutions per minute. The method for preparing the piezoelectric ceramic tube further includes: aging the piezoelectric ceramic obtained after the high-voltage polarization at room temperature for 24 hours, and then performing a performance test.
12. A piezoelectric ceramic tube, characterized in that: The piezoelectric ceramic tube is prepared according to the method for preparing a piezoelectric ceramic tube according to any one of claims 7 to 11.
13. Use of the piezoelectric ceramic tube according to claim 12, characterized in that: The piezoelectric ceramic tube is applied in the field of display technology, and the field of display technology is the field of laser display technology; The laser display technology includes a laser display device, the laser display device includes a fiber scanner, the fiber scanner includes an actuator, and the piezoelectric ceramic tube is configured as the actuator.